(untitled) (American Journal of Technology and Applied Sciences, 2022)
At present, in the areas where the geographical location of the planned land area plays a role in the research work, scientific and research work is being carried out aimed at developing new scientific and technical solutions for the organization of optimal use of agricultural land. In this direction, among other things, reducing the harmful effects of the environment in areas with a risk of wind erosion, improving the methods of effective use of each plot of land, taking into account the natural and economic conditions and the requirements for protecting the land from erosion, developing geosystem complexes that allow to prevent erosion during land construction. , it is urgent to create technologies that allow effective use of land, protection of soils from erosion, and increase of land productivity.